9. Penerapan Model Pembelajaran Kooperatif Tipe Snawball Throwing Pada Tema Kerukunan Dalam Bermasyarakat Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - ., Ngatmini; Gregorius, Jandut; Gregorius, Jandut (JURNAL WAHANA PENDIDIKAN DASAR, 2017)
Civic learning in 5th grade SDN PLOSO III Surabaya still packed conventionally. The teacher much be speech than the  activity study the student be passive. Even less Civic learning implemented in the form of exercise ?the main bench mark? student achievement . therefore it, researchers do updates presentation Civic learning through the implementation of the model cooperative learning type snowball throwing for ancerl result study of the student. This research for description effect of applaying the model cooperative learning type snowball throwing in Civic learning on learning result study of the student at 5th grade SDN PLOSO III Surabaya. Research subject are student of 5th grade wich amount 28 types of research is action to research class amount 2 siklus. Every siklus implemented pass through 4 sesion, are planning, implementer, observasion, and refleksion in every siklus. Research of data result of observasion and exercise. Observasion of the data activity teacher and student in applaying the model learning direct analysed in presentage. Result study of the student analysised of presentage completeness of classical learning. Research of result point out that activity student every follow learning experience increase as big as 14,3 % are from 78,6% in I siklus be 92,9% in II siklus. The teacher activities in research experience in crease quality up to 22,2% are from 66,7% in I siklus be 88,9% in Iisiklus. Result of student of student experience as big as 14,3% are from 75% in I siklus be 89,3% in II siklus. Be based on research of result, then propocition for teacher for try apply the model cooperative learning type snowball throwing in civic learning for rise product learn the student. Key words : The model cooperatife type snowball throwing ,civic and the rise of the study.